Network Pharmacology and Molecular Docking Analysis of Fagonia cretica Compounds as Chemopreventive Agents in Luminal Breast Cancer - Eman Jehangir; Afifah Nur Rizqi; Syedah Ruqayyah Hadiyah; Anwar Rovik (Jurnal Tumbuhan Obat Indonesia, 2025)
Breast cancer remains a public health issue. In Pakistan, breast cancer cases continue to rise annually.Tamoxifen is a standard treatment for patients with luminal breast cancer (ER+); however, prolong use oftamoxifen cause side effects and may lead to drug resistance. Therefore, there is an urgent need to explorenatural compounds as safer chemopreventive agents. This study uses computational methods to investigatecompounds from Fagonia cretica and their potential interactions with molecular targets relevant to luminalbreast cancer. We combined a literature review, network pharmacology, and molecular docking to identifypromising therapeutic agents from Fagonia cretica. The plant contains various natural compounds, mainlyfound in its aerial parts. Several compounds are frequently reported, including isorhamnetin, oleanolic acid,gallic acid, kaempferol, and apigenin. These compounds meet favorable drug-like characteristics. Networkpharmacology analysis indicated that these compounds target several key cancer-related proteins andpathways, including CA12, AURKB, CDK1, PLK1, MMP9, NEK2, TOP2A, CCNB1, CCNB2, and ESR1.Kaempferol exhibited good binding affinities in molecular docking simulations for key protein targets: CDK1(-7.39 kcal/mol), ESR1 (-7.73 kcal/mol), and MMP9 (-7.29 kcal/mol). Our findings suggest that Fagoniacretica has potential as a multitarget chemopreventive agent in luminal breast cancer. Keywords: breast cancer, ethnomedicine, Fagonia cretica, targeted therapy